A Comparative Study of Strategic Planning Practices of SMEs and Large‐Sized Business Organizations in Emerging Economies: The Case of UAE1. (November 2015) - Muhammad Siddique, C.
Abstract : While SMEs in the emerging economy of UAE have begun to use strategic planning tools such as financial analysis, PEST analysis, cost–benefit analysis, and core and distinctive competency analysis, they are still far behind large‐sized business organizations.